A new species of Sarcohyla (Anura: Hylidae: Hylini) from the Sierra Madre del Sur of Guerrero and Estado de México, México - Kaplan, Moises; Heimes, Peter; Aguilar, Rafael (Zootaxa, 2020)
We describe a new species of frog Sarcohyla floresi sp. nov. from the Sierra Madre del Sur of Guerrero and the southern part of Estado de México, based on specimens previously referred to as S. pentheter and newly obtained specimens. The new species has stream-dwelling tadpoles with labial tooth row formula 2(2)/3 and adults with a distinctive dark dorsolateral band bordered by a white line. S. floresi can be included in the S. bistincta group.